Both babies with sirenomelia’ in twin pregnancy: a case report and review of literature - Chowdhury, Soham; Kundu, Sarmila; Manna, Satyendu Sekhar; Das, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sirenomelia, also called as ‘Mermaid syndrome’, is a rare congenital malformation of uncertain aetiology. It is characterised by fusion of the lower limbs and commonly associated with severe urogenital and gastrointestinal malformation. We report a case of twin pregnancy with both babies had sirenomelia. No previous case of ‘both babies with sirenomelia’ in twin pregnancy has been reported till date.